Do CVID patients on SCIG have more autoimmune (thrombo)cytopenic events than CVID patients on IVIG? - Camacho-Ordonez, Nadezhda; Hirsch, Aleksandra; Campos, Luiza; Goldacker, Sigune; Burns, Siobhan O.; Moreira, Fernando; Warnatz, Klaus; Grimbacher, Bodo (Frontiers in Immunology, 2025)
Autoimmune thrombocytopenia (AITP) is frequent in patients diagnosed with common variable immunodeficiency (CVID). High dose intravenous immunoglobulin treatment (IVIG) has conventionally been a cornerstone of the initial therapy for AITP. This study aimed to assess the safety and effectiveness of subcutaneous immunoglobulin (SCIG) compared to IVIG in preventing AITP in CVID patients. This prospective observational study enrolled 47 adult CVID patients concurrently diagnosed with AITP. Of the participants, 27 (57%) were treated with SCIG, while 20 (43%) received IVIG. AITP episodes were defined as platelet counts <50,000/µl with bleeding or <20,000/µl with or without bleeding, followed over a 64-month period. Among the 47 patients included, 12 (25.5%) experienced AITP episodes, with seven using SCIG and five using IVIG. No significant difference was observed in AITP occurrence between the two treatment groups (p-value=0.99). Neither splenomegaly nor the use of immunosuppressive therapies showed a correlation to the AITP bouts. Maintaining IgG trough levels above 7g/l arose as a key factor for preventing AITP in both treatment modalities. In conclusion, both SCIG and IVIG demonstrated comparable efficacy in the prevention of AITP in CVID patients. This study highlights the importance of monitoring IgG levels in the management of CVID patients with AITP.